Knowledge gaps and research priorities in tuberculous meningitis - Seddon, JA; Wilkinson, R; van Crevel, R; Figaji, A; Thwaites, GE; Tuberculous Meningitis International Research Consortium (F1000Research, 2019)
Tuberculous meningitis (TBM) is the most severe and disabling form of tuberculosis (TB), accounting for around 1-5% of the global TB caseload, with mortality of approximately 20% in children and up to 60% in persons co-infected with human immunodeficiency virus even in those treated. Relatively few centres of excellence in TBM research exist and the field would therefore benefit from greater co-ordination, advocacy, collaboration and early data sharing. To this end, in 2009, 2015 and 2019 we convened the TBM International Research Consortium, bringing together approximately 50 researchers from five continents. The most recent meeting took place on 1 st and 2 nd March 2019 in Lucknow, India. During the meeting, researchers and clinicians presented updates in their areas of expertise, and additionally presented on the knowledge gaps and research priorities in that field. Discussion during the meeting was followed by the development, by a core writing group, of a synthesis of knowledge gaps and research priorities within seven domains, namely epidemiology, pathogenesis, diagnosis, antimicrobial therapy, host-directed therapy, critical care and implementation science. These were circulated to the whole consortium for written input and feedback. Further cycles of discussion between the writing group took place to arrive at a consensus series of priorities. This article summarises the consensus reached by the consortium concerning the unmet needs and priorities for future research for this neglected and often fatal disease.